2003
DOI: 10.1124/jpet.103.048751
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Recognition of Substrates by the Human andDrosophilaSerotonin Transporters

Abstract: The human and Drosophila serotonin transporters (hSERT and dSERT, respectively) were used to explore differences in substrate properties. hSERT and dSERT showed similar K m values for 5-hydroxytryptamine (5-HT; serotonin) transport (1.2 and 0.9 M, respectively), suggesting similar recognition of 5-HT by the two species variants. Although dSERT cell surface expression was approximately 8-fold lower than that of hSERT, dSERT does appear to have a 2-fold faster turnover number for inward transport of 5-HT. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…4B). A lack of substrateinduced efflux is characteristic of channels and may indicate that the A169D mutant and dSERT are operating in a channel-like mode (Rodríguez et al, 2003). This finding may suggest that the aspartate in position 169 is involved with gating SERT channel-like properties.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…4B). A lack of substrateinduced efflux is characteristic of channels and may indicate that the A169D mutant and dSERT are operating in a channel-like mode (Rodríguez et al, 2003). This finding may suggest that the aspartate in position 169 is involved with gating SERT channel-like properties.…”
Section: Discussionmentioning
confidence: 77%
“…Previous work by our group has demonstrated that amphetamines were poorly transported by and unable to induce substrate efflux at the dSERT (Rodríguez et al, 2003). Of the five hSERT mutants constructed with a dSERT residue, only the A169D mutant gained a net negative charge.…”
Section: Transport Kinetics Of Hsert Tmh III Mutantsmentioning
confidence: 98%
“…Partial inhibitory effects by tetraethylammonium, guanidine, l-carnitine, and thiamine were observed in TR-BBB13 and TR-CSFB3 cells, but not in PMATexpressing CHO cells, suggesting that endogenous transporters beside PMAT in these brain barrier cells were related to these inhibitory effects. Indeed, MPP + has been reported to be a substrate for not only PMAT but also OCT1-3, 36-38 DAT, 39 SERT, 40 and OCTN2. 41 Of these transporters, rOCTN2 mRNA was expressed at a relatively high level in both TR-BBB13 and TR-CSFB3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…When 3-phenyltropane analogs were assayed, the cells were preincubated with drug at 37°C for 10 min. This preincubation was not included when the substituted amphetamines were assayed, because these compounds have been shown to be substrates for SERT, and the intracellular accumulation of drug could affect 5-HT transport (Wall et al, 1995;Rodriguez et al, 2003). [ 3 H]5-HT (ϳ110 Ci/mmol) was diluted to yield a final assay concentration of 20 nM in KRH buffer supplemented with 100 M Lascorbic acid and 100 M pargyline.…”
Section: Methodsmentioning
confidence: 99%
“…The H 1-281 D 282-476 H 477-638 chimera was generated as described previously (Rodriguez et al, 2003). Briefly, it is a full-length 638 amino acid transporter, constructed from amino acids 1-281 and 477-638 with identity from hSERT and residues 282-476 with identity from dSERT.…”
Section: Methodsmentioning
confidence: 99%